Social inequalities in sleep‐disordered breathing: Evidence from the CoLaus|HypnoLaus study. (25th November 2018) - Petrovic, Dusan; Haba‐Rubio, José; Carmeli, Cristian; Vollenweider, Peter; Heinzer, Raphaël; Stringhini, Silvia
Abstract: Sleep‐disordered breathing is a common condition, related to a higher cardiometabolic and neurocognitive risk. The main risk factors for sleep‐disordered breathing include obesity, craniofacial characteristics, male sex and age. However, some studies have suggested that adverse socioeconomic circumstances and lifestyle‐related behaviours such as smoking and alcohol use, may also be risk factors for sleep‐disordered breathing. Here, we investigate the associations between socioeconomic status and sleep‐disordered breathing, as measured by sleep apnea–hypopnea and oxygen desaturation indexes. Furthermore, we assess whether these associations are explained by lifestyle‐related factors (smoking, sedentary behaviour, alcohol use and body mass index [BMI]). We used data from the CoLaus|HypnoLaus study, a population‐based study including 2162 participants from Lausanne (Switzerland). Socioeconomic status was measured through occupation and education. Sleep‐disordered breathing was assessed through polysomnography and measured using the apnea–hypopnea index (AHI: number of apnea/hypopnea events/hr: ≥15/≥30 events), and the ≥3% oxygen desaturation index (ODI: number of oxygen desaturation events/hr: ≥15/≥30 events). Lower occupation and education were associated with higher AHI and ODI (occupation: AHI30, odds ratio (OR) = 1.88, 95% confidence interval (CI) [1.07; 3.31]; ODI30, OR = 2.29, 95% CI [1.19; 4.39]; education: AHI30, OR = 1.21, 95% CI [0.85; 1.72]; ODI30, OR = 1.26, 95% CI [0.83; 1.91]). BMI was associated with socioeconomic status and AHI/ODI, and contributed to the socioeconomic gradient in SDB, with mediation estimates ranging between 43% and 78%. In this Swiss population‐based study, we found that low socioeconomic status is a risk factor for sleep‐disordered breathing, and that these associations are partly explained by BMI. These findings provide a better understanding of the mechanisms underlying social differences in sleep‐disordered breathing and may help implement policies for identifying high‐risk profiles for this disorder.